Catalan legal acts and documents related to the region`s independence process in the context of the radicalization of independentism. Selected examples from 2012-2017 - Husar-Poliszuk, Wioletta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article tackles the issue of normative acts and documents passed by the Catalan parliament that are part of the region`s independence process. The subject of the study includes the laws and declarations that caused the most controversy and were adopted between 2012 and 2017, the most turbulent period for Catalonia in political and social terms. Importantly, they are analyzed in the context of the radicalization process of Catalan independentism.
Keywords: Catalonia; independence movement; Catalan independentism; Catalan parliament; Catalan-Spanish conflict